Specialised lithic technology of terminal Pleistocene maritime peoples of Wallacea. (December 2018) - Maloney, Tim Ryan; Mahirta,; O'Connor, Sue; Reepmeyer, Christian
Abstract: Excavation in Tron Bon Lei shelter on the Indonesian Island of Alor has uncovered a rich Pleistocene lithic assemblage, which includes obsidian artefacts representing a specialised industry previously undetected in any early stone tool assemblage of Island South East Asia (ISEA). Portable X-ray florescence of the obsidian assemblage has revealed three discrete sources, and that at least one of the sources is likely off-island. This indicates that inter-island exchange networks were active from the terminal Pleistocene onwards. Obsidian from all sources was reduced exclusively using bipolar anvil-resting techniques, resulting in the production of exceptionally small bipolar cores and flakes. The assemblage reveals extraordinary effort to reduce the obsidian, with cores being typically smaller than ten millimetres, and many around six millimetres at discard. Using reduction sequence analyses and technological observations, we document this specialised industry and discuss the role these artefacts may have played in the lifeways of the people of Alor Island. Graphical abstract: Highlights: Specialised obsidian bipolar reduction from terminal Pleistocene to late Holocene. Remarkably stable bipolar technology possibly used in shell bead/hook working. Local and imported obsidian used in conjunction with expedient basalt tools. Total lack of morphological change in local and inter-island transported obsidian.